Tata Laksana Neurogenic Bladder akibat Cedera Saraf Spinal: Tinjauan Pustaka - ., Muvida; Mustikasari, Hanif (Cermin Dunia Kedokteran, 2025)
Neurogenic bladder is one of the most common complications of spinal cord injury (SCI), leading to impaired voiding function, recurrent urinary tract infections, and reduced quality of life. Determining the location, extent, and severity of the lesion is essentialto tailor management strategies to each patient’s neurological condition and functional status. Treatment includes non-surgical approaches such as intermittent catheterization, neuromodulation, and pharmacological therapy using anticholinergic drugs or 3-adrenergic agonists, which have been shown to reduce detrusor pressure. In cases unresponsive to conservative therapy,surgical interventions such as bladder augmentation or sacral nerve stimulation may be performed to preserve renal function, prevent vesicoureteral reflux, and achieve urinary continence. The prognosis is generally favorable when patients undergo longterm rehabilitation combined with comprehensive education and regular renal function monitoring. Multidisciplinary collaboration among urologists, rehabilitation specialists, and nurses plays a vital role in improving patient quality of life, reducing complications, and ensuring sustainable, effective management.